2019
DOI: 10.1089/ast.2018.1897
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Life and the Habitability of Mars: The ESA Space Experiment BIOMEX on the ISS

Abstract: BIOMEX (BIOlogy and Mars EXperiment) is an ESA/Roscosmos space exposure experiment housed within the exposure facility EXPOSE-R2 outside the Zvezda module on the International Space Station (ISS). The design of the multiuser facility supports—among others—the BIOMEX investigations into the stability and level of degradation of space-exposed biosignatures such as pigments, secondary metabolites, and cell surfaces in contact with a terrestrial and Mars analog mineral environment. In parallel, analysis on the via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 64 publications
1
78
0
2
Order By: Relevance
“…Earth is an obvious source of living organisms that may have been ejected, jettisoned, cast into space, only to crash onto the surface of other worlds in this solar system beginning over 3.8 bya, thereby repeatedly seeding Venus, Mars, and other planets with life (Beech et al 2018;Fajardo-Cavazosa et al 2007;Hara et al 2010;Melosh 2003;Mileikowsky et al 2000a,b;Schulze-Makuch et al 2005) and vice-versa. Asteroids and meteors striking Earth may have repeatedly sheared away masses of earth and rock, and blasted this material (and presumably any adhering microbes, fungi, algae, and lichens) into space (Beech et al 2018;Gladman et al 1996;Hara et al 2010;Melosh 2003;Mileikowsky et al 2000a,b), where they can survive (Horneck et al 2002;Onofri et al 2012;De Vera et al 2019;De la Torre Noetzel et al 2020;Novikova 2009;Novikova et al 2016;Olsson-Francis et al 2009). Some of this microbeladen debris may have later crashed on Mars (Hara et al 2010;Schulze-Makuch et al 2005) where, as demonstrated by simulation studies, a variety of organisms can also survive (Cockell et al 2005;Mahaney and Dohm 2010;Osman et al 2008;Pacelli et al 2016;Sanchez et al 2012;Selbman et al 2015); and the same may be true of organisms deposited in the upper clouds of Venus (Joseph 2019;Konesky 2009;Limaye et al 2018;Sagan and Morowitz 1967;Schulze-Makuch et al 2004).…”
Section: Surviving Impact Ejection Exposure To Space and Crash Landingmentioning
confidence: 99%
“…Earth is an obvious source of living organisms that may have been ejected, jettisoned, cast into space, only to crash onto the surface of other worlds in this solar system beginning over 3.8 bya, thereby repeatedly seeding Venus, Mars, and other planets with life (Beech et al 2018;Fajardo-Cavazosa et al 2007;Hara et al 2010;Melosh 2003;Mileikowsky et al 2000a,b;Schulze-Makuch et al 2005) and vice-versa. Asteroids and meteors striking Earth may have repeatedly sheared away masses of earth and rock, and blasted this material (and presumably any adhering microbes, fungi, algae, and lichens) into space (Beech et al 2018;Gladman et al 1996;Hara et al 2010;Melosh 2003;Mileikowsky et al 2000a,b), where they can survive (Horneck et al 2002;Onofri et al 2012;De Vera et al 2019;De la Torre Noetzel et al 2020;Novikova 2009;Novikova et al 2016;Olsson-Francis et al 2009). Some of this microbeladen debris may have later crashed on Mars (Hara et al 2010;Schulze-Makuch et al 2005) where, as demonstrated by simulation studies, a variety of organisms can also survive (Cockell et al 2005;Mahaney and Dohm 2010;Osman et al 2008;Pacelli et al 2016;Sanchez et al 2012;Selbman et al 2015); and the same may be true of organisms deposited in the upper clouds of Venus (Joseph 2019;Konesky 2009;Limaye et al 2018;Sagan and Morowitz 1967;Schulze-Makuch et al 2004).…”
Section: Surviving Impact Ejection Exposure To Space and Crash Landingmentioning
confidence: 99%
“…The search for extraterrestrial life forms has given rise to numerous space missions that have enabled researchers to collect data, test different species of extremophiles (e.g., black fungi, cyanobacteria, bryophytes, invertebrates) in space conditions, analyse their physiology [29] in extreme conditions, and finally find potentially habitable exoplanets for Earth-like organisms. Space missions which previously studied extremophiles include EXPOSE-E, EXPOSE-R2, BIOMEX, and CoRoT [30].…”
Section: Discussionmentioning
confidence: 99%
“…A combined effort of 20 nations was started in 2014 with a Soyuz Rocket to the International Space Station (ISS), designated as BIOMEX [117]. Samples from more than 20 experiments were analyzed.…”
Section: Habitable Zonesmentioning
confidence: 99%